The Influence of the AIR (Auditor Intellectually Repetition) Model on Middle School Students' Interest in Learning Islamic Religious Education - Rizka Mirda Aulia; Erlina; Sunarto (DIDAKTIKA, 2025)
The low interest of students in learning Islamic Religious Education (PAI), especially in the indicator of "preferring statements", is an important concern in the world of education today. Minimal interaction with the material, limited variety of learning activities, and the dominant use of conventional methods that are one-way are the main factors in the low enthusiasm for learning of students. This study aims to determine the effect of the Auditor Intellectually Repetition (AIR) learning model on students' interest in learning Islamic Religious Education (PAI) at SMP Negeri 1 Bandar Lampung. The AIR model emphasizes three main aspects, namely Auditory (listening), Intellectually (thinking), and Repetition (repetition) which are designed to encourage active and enjoyable student involvement. This study uses a quantitative approach with a quasi-experimental method and a post-test only control group design. The research sample was selected through simple random sampling, consisting of two classes: the experimental class (VII 3) which received the AIR model treatment and the control class (VII 5) with conventional learning. The research instrument was a non-test questionnaire with a Likert scale on the indicator of "preferring statements". Data were analyzed using a pooled variance t-test after meeting normality and homogeneity requirements. The results showed a significant effect of the AIR model with a significance value of 0.000, indicating that this model was effective in increasing interest in learning Islamic Religious Education (PAI).